Potential use of sugar cane bagasse ash as sand replacement for durable concrete. (July 2021) - Torres de Sande, Veronica; Sadique, Monower; Pineda, Paloma; Bras, Ana; Atherton, William; Riley, Mike
Abstract: The increasing urban development, led by concrete, requires a higher availability of materials and energy, and it will be responsible for a high waste generation. To face the exploitation of natural resources, the use of fossil fuels and the reduction of waste disposal, new environmental-friendly strategies emerge accomplishing the circular economy principles. In this research, the use of poor reactive agro-industrial ashes as sand replacement in cement-based materials is investigated. Poor reactive sugar cane bagasse ashes (fly and bottom ash -SCB FA and SCB BA, respectively) from a power plant in Dominican Republic have been used in substitution rates of 10%, 20% and 30% of weight of sand. Physico-chemical characteristics of ashes are investigated and correlated to the performance of the bio-concretes. SCB FA showed being an enhancer of durability-related properties of the concrete even with high content of silica in form of quartz, due to the capability of modifying the microstructure of the concrete and an additional binding capacity of chlorides ions. Durability-related tests (open porosity test, electrical resistivity test, capillary absorption test and chloride migration test) have been conducted at 28, 60, 90 and 240days. Direct correlations exist when compared chloride migration resistance against porosity and electrical resistivity in concretes with SCB FA, not so for capillary absorption. This demonstrates the inadequacy of establishing conclusions about durability performance of bio-concretes based on durability tests when run independently. The use of agro-industrial ashes as substitutes of natural aggregates not only reduces the consumption of natural sand but can deliver bio-concretes with potential benefits in terms of compressive strength and durability. Highlights: Concretes containing SCBA (SCB FA and SCB BA) as sand replacement were characterised. Low-treated industrial SCBA showed potential uses in concrete production as sand replacement. SCB FA provided enhanced durability-related properties in proportion to the substitution rate. SCB BA have potential uses when non durability properties are required, and w/c applied. Concrete properties correlations were found.